The evolution of Calpurnia Tate - Kelly, Jacqueline (Square Fish, 2011)
In central Texas in 1899, eleven-year-old Callie Vee Tate is instructed to be a lady by her mother, learns about love from the older three of her six brothers, and studies the natural world with her grandfather, the latter of which leads to an important discovery.